Annual Report on Registration of Births and Deaths 1994 Goa State - Planning Commission (Planning Commission, 1994)
The Deaths Report in Form No. 4 in variably accompanied by the Medical Certificate of Cause of death in Form No.8, if the deceased during his last illness was attended by a Medical Practitioner or in Form 8A, in case the deceased died in a medical institution. However in those cases where the deceased was not attended by a Medical Practitioner, the Registrars have been instructed to ascertain the cause death for which purpose a list of important causes of death has been provided to them.
Goa State